HUBUNGAN TINGKAT USIA DENGAN DISIPLIN BELAJAR MAHASISWA MADRASAH DINIYAH SEMESTER VIII DI UNIVERSITAS PESANTREN TINGGI DARUL ‘ULUM - Ali Muhsin (Universitas Islam Lamongan, 2017)
Age is one of the important factors in learning and developing the potentials of human beings. The discipline of learning is a state in which the student is in an orderly, orderly manner and as it should be. Problems in this study is How the age level, How the level of discipline to learn, Is there a correlation between the level of age with the discipline of learning Students Madrasah Diniyah semester VIII even in Unipdu Jombang 2016/2017. This research includes field research research with quantitative approach with product moment correlation analysis. Based on the calculation is known that rxy = 0.246 for the error rate set 5% (95% confidence set) and N = 30 and rtabel ¬ 0.361 And it turns out that rhitung smaller than the rtabel, in other words between variables X and variable Y no relationship. That rhitung≤ rtabel, then Ha